Consumer Legal Protection Against Defaults in Music Concert Ticket Purchase Deposit Service - Anggraeni, Dita Puspita; Sholihah, Agustina Kumala Dewi (Et-Tijarie, 2025)
Music concert deposit service is a service that provides services to consumers to buy a ticket outside of the original seller of a concert, where the role of music concert deposit service in Indonesia is still many who are interested in using this service. The purpose of this study is to explain the responsibility efforts of service actors to purchase Coldplay music concert tickets and their legal implications for aggrieved consumers as well as a review of defaults against the sale and purchase of Coldplay music tickets in the concept of Sharia maqasid. The research method used in this study is empirical with a sociological juridical approach, the types and sources of data are divided into two, namely primary data and secondary data. Primary data were obtained through observation, interviews and the internet. Secondary data is in the form of documents such as laws and related records. It is then analyzed through the stages of editing, classification, verification, analysis, and conclusion to ensure the validity and relevance of the data. This study shows the results that efforts are made to compensate consumers and consumers get protection from litigation channels in accordance with the Consumer Protection Law and the ITE Law. Acts of default are contrary to the principles of hifz al-mal (protection of property), raf' al-zulm (prevention of tyranny), and maslahah (common good). If the perpetrator does not fulfill his responsibilities can be subject to criminal or civil legal sanctions.